ANALYSIS AND STRUCTURAL INVESTIGATIONS ON NEOLITHIC PAINTED POTTERY FROM SUPLACU DE BARCĂU/PORŢ-CORĂU ARCHAEOLOGICAL SITE - CARSTEA (ELEKES), ANAMARIA; GLIGOR, MIHAI; BUCURICA, IOAN ALIN; DULAMA, IOANA DANIELA; RADULESCU, CRISTIANA; STIRBESCU, RALUCA MARIA; STANESCU, SORINA GEANINA; GHEBOIANU, ANCA IRINA (Journal of the sciences and arts, 2024)
The main objective of this study was the archaeometric analysis of eleven ceramic fragments discovered in the archaeological site of Suplacu de Barcău/Porț-Corău, situated in the Northwest part of Romania, more precisely in the Sylvanian Basin. The ceramic fragments come from different archaeological contexts and show a typically decoration, through black painting. The studied ceramic fragments have fine and semi-fine textures, discovered in certain stratigraphic situations: funerary contexts or household pits. All the analysed fragments belong to the Suplac type pottery. The archaeological research, both systematic and preventive, highlighted the main characteristics of the Neolithic habitation in the Sylvanian Basin, making it the subject of numerous studies until now. In the present paper, optical microscopy, scanning electron microscopy coupled with energy dispersive spectrometry (SEM-EDS) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) analyses were carried out on the batch of ceramic pieces studied, and based on the obtained results, the burning temperature of the samples was estimated. At the same time, for five clay samples – collected from archaeological sites and around the settlement – the elemental content was determined to establish the potential source of clay for the ceramic fragments.